Spanning Fermi arcs in a two-dimensional magnet - Chen, Ying-Jiun; Hanke, Jan-Philipp; Hoffmann, Markus; Bihlmayer, Gustav; Mokrousov, Yuriy; Bluegel, Stefan; Schneider, Claus M.; Tusche, Christian (Nature Communications, 2022)
The discovery of topological states of matter has led to a revolution in materials research. When external or intrinsic parameters break symmetries, global properties of topological materials change drastically. A paramount example is the emergence of Weyl nodes under broken inversion symmetry. While a rich variety of non-trivial quantum phases could in principle also originate from broken time-reversal symmetry, realizing systems that combine magnetism with complex topological properties is remarkably elusive. Here, we demonstrate that giant open Fermi arcs are created at the surface of ultrathin hybrid magnets where the Fermi-surface topology is substantially modified by hybridization with a heavy-metal substrate. The interplay between magnetism and topology allows us to control the shape and the location of the Fermi arcs by tuning the magnetization direction. The hybridization points in the Fermi surface can be attributed to a non-trivial mixed topology and induce hot-spots in the Berry curvature, dominating spin and charge transport as well as magneto-electric coupling effects.
CRIS-Team Scopus Importer:2023-03-27